Differentiated learning innovation assisted by wordwall media in mathematics learning - Dina Febrianita; Nuhyal Ulia; Rochelle Diaz Naniong (Jurnal Ilmiah Profesi Guru (JIPG), 2025)
This study aims to examine differentiated learning innovation assisted by Wordwall media in mathematics learning in grade VI of state elementary school Banyumanik 03. The main problem identified is the low motivation and participation of students in mathematics learning materials. To overcome this, a differentiated learning approach was developed that adapts to the learning styles and needs of students, with the support of Wordwall as an interactive medium to increase engagement and enthusiasm for learning. This study used a qualitative method with a case study approach involving 28 sixth-grade students. Data were collected through observation, interviews, and analysis of learning outcomes. The results showed that the implementation of differentiated learning assisted by Wordwall significantly increased student motivation and participation in learning, as indicated by an increase in the average learning outcome score from 56 to 90. In addition, the use of Wordwall also helped teachers in classroom management and provided more effective feedback.Inovasi pembelajaran berdiferensiasi berbantuan media wordwall dalam pembelajaran matematikaPenelitian ini bertujuan untuk mengkaji inovasi pembelajaran berdiferensiasi berbantuan media Wordwall dalam pembelajaran matematika di kelas VI SDN Banyumanik 03. Permasalahan utama yang diidentifikasi adalah rendahnya motivasi dan partisipasi peserta didik terhadap materi pembelajaran matematika. Untuk mengatasinya, dikembangkan pendekatan pembelajaran berdiferensiasi yang menyesuaikan gaya dan kebutuhan belajar peserta didik, dengan dukungan Wordwall sebagai media interaktif guna meningkatkan keterlibatan dan semangat belajar. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus yang melibatkan 28 peserta didik kelas VI. Data dikumpulkan melalui observasi, wawancara, dan analisis hasil belajar. Hasil penelitian menunjukkan bahwa penerapan pembelajaran berdiferensiasi berbantuan Wordwall dapat meningkatkan motivasi dan partisipasi belajar peserta didik secara signifikan, yang ditunjukkan oleh peningkatan nilai rata-rata hasil belajar dari 56 menjadi 90. Selain itu, penggunaan Wordwall juga membantu guru dalam pengelolaan kelas dan pemberian umpan balik yang lebih efektif.